2021
DOI: 10.1007/s12020-021-02834-7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic angiotensin receptor activation promotes hepatic triacylglycerol accumulation during an acute glucose challenge in obese-insulin-resistant OLETF rats

Abstract: Purpose Angiotensin receptor blockers (ARBs) can ameliorate metabolic syndrome (MetS)-associated dyslipidemia, hepatic steatosis, and glucose intolerance, suggesting that angiotensin receptor (AT1) over-activation contributes to impaired lipid and glucose metabolism, which is characteristic of MetS. The aim of this study was to evaluate changes in the lipid profile and proteins of fatty acid uptake, triacylglycerol (TAG) synthesis, and β-oxidation to better understand the links between AT1 overac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“… 38 Meanwhile, Ang II can aggravate IR though activating insulin signaling pathways. 39 Yuan et al 40 found that mice with hypertension showed more severe LF than those without hypertension, and that cytokine activation and inflammation played an important role. RAS activation, IR, and inflammation are important pathophysiological mechanisms underlying the co-morbidity of hypertension and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Meanwhile, Ang II can aggravate IR though activating insulin signaling pathways. 39 Yuan et al 40 found that mice with hypertension showed more severe LF than those without hypertension, and that cytokine activation and inflammation played an important role. RAS activation, IR, and inflammation are important pathophysiological mechanisms underlying the co-morbidity of hypertension and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some analyses were performed in younger animals initially to gain further insights. Basic metabolic changes are summarized in Table 2 18,22,25,26 . In brief, all presented parameters were elevated in OLETF rats at 16 weeks of age when compared to age‐matched control (LETO) rats and ARB treatment normalized the elevated SBP and plasma glucose levels.…”
Section: Resultsmentioning
confidence: 99%
“…Younger animals were 10 week old males divided into the following groups: (1) untreated control + vehicle (0.5% methylcellulose by oral gavage once daily), (2) untreated OLETF + vehicle, and (3) OLETF + ARB (ARB; 10 mg olmesartan/kg/day by oral gavage × 6 weeks) and were approximately 16 weeks at dissection 18,22 . Older animals were 17 week old males divided into the same three groups with the exception that older animals were treated with ARB for 8 weeks and were ~25 weeks at dissection 25,26 . Olmesartan was selected as the ARB of choice in the primary studies because it is more effective at ameliorating T2D‐associated renal injury and hypertension than other ARBs 60 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations